Peristaltic flow of MHD Jeffrey fluid through finite length cylindrical tube - Tripathi D.; Ali N.; Hayat T.; Chaube M.K.; Hendi A.A. (My University, 2025)
The present investigation studies the peristaltic flow of the Jeffrey fluid through a tube of finite length. The fluid is electrically conducting in the presence of an applied magnetic field. Analysis is carried out under the assumption of long wavelength and low Reynolds number approximations. Expressions of the pressure gradient, volume flow rate, average volume flow rate, and local wall shear stress are obtained. The effects of relaxation time, retardation time, Hartman number on pressure, local wall shear stress, and mechanical efficiency of peristaltic pump are studied. The reflux phenomenon is also investigated. The case of propagation of a non-integral number of waves along the tube walls, which are inherent characteristics of finite length vessels, is also examined. © 2011 Shanghai University and Springer-Verlag Berlin Heidelberg.